2022
DOI: 10.1080/21655979.2022.2079242
|View full text |Cite
|
Sign up to set email alerts
|

Knocking down ETS Proto-oncogene 1 (ETS1) alleviates the pyroptosis of renal tubular epithelial cells in patients with acute kidney injury by regulating the NLR family pyrin domain containing 3 (NLRP3) transcription

Abstract: Acute kidney injury (AKI) has a high mortality rate, but its pathogenesis remains unclear Lipopolysaccharide (LPS)-mediated renal tubular epithelial pyroptosis is involved in the pathogenesis of AKI. NLR family of pyrin domains containing 3 (NLRP3) plays an important role in pyroptosis. To further understand the transcriptional regulation mechanism of NLRP3, the peripheral blood of patients with AKI was analyzed in this study, showing that the levels of NLRP3 and cell pyroptosis in patients with AKI were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“… 50 In acute kidney injury patients, knocking down ETS1 will alleviate the pyroptosis of renal tubular epithelial cells. 51 In this study, we found that the expression levels of SEPTIN1, CD3G, and ETS1 were up-regulated. Moreover, correlation analysis showed that the expression levels of SEPTIN1, CD3G, and ETS1 were significantly negatively correlated with monocyte abundance.…”
Section: Discussionmentioning
confidence: 51%
“… 50 In acute kidney injury patients, knocking down ETS1 will alleviate the pyroptosis of renal tubular epithelial cells. 51 In this study, we found that the expression levels of SEPTIN1, CD3G, and ETS1 were up-regulated. Moreover, correlation analysis showed that the expression levels of SEPTIN1, CD3G, and ETS1 were significantly negatively correlated with monocyte abundance.…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, we screened the up-regulated TFs in SCI which could regulate NLRP3/PRGs, to find potential targets for inhibiting SCI pyroptosis. A total of 39 TFs were screened out, 16 of which have been reported to be involved in regulating pyroptosis: ERG ( Yao et al, 2022 ), FLI1 ( Li et al, 2018 , 2019 ), FOXM1 ( Xu et al, 2021 ), HIC1 ( Gao et al, 2021 ), JUN ( Wang et al, 2020 ), KLF4 ( Xiong et al, 2021 ), USF2 ( Sun et al, 2022 ), STAT2 ( Wang et al, 2022 ), FOS ( Wang et al, 2021 ), NFATC1 ( Kai et al, 2020 ), MYC ( Gaikwad et al, 2020 ), NFE2L2 ( Ling et al, 2021 ), SMAD3 ( Zhu et al, 2020 ), ETS1 ( Juan et al, 2022 ), IKZF1 ( Kadono et al, 2022 ), and HMGA1 ( Liang et al, 2022 ). In addition, we performed KEGG Pathway Analysis on these 39 TFs, which were enriched into multiple signaling pathways, such as MAPK signaling pathway, Wnt signaling pathway, JAK-STAT signaling pathway, and Toll-like receptor signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Knocking down C/EBPβ inhibits the NLRP3 inflammasome-mediated Caspase-1 signaling pathway by inactivating the TFAM/advanced glycation end-products pathway. The interaction of C/EBPβ and TFAM promotes pyroptosis by activating the NLRP3/Caspase-1 signaling axis, thereby promoting the occurrence of AKI [64]. TRAF-interacting protein with forkhead-associated domain is also involved in pyroptosis by activating mitochondrial damage and may be a therapeutic target to treat SA-AKI [43].…”
Section: Ischemia-reperfusion Injury Akimentioning
confidence: 99%
“…Transcription factors may also play an essential role in the signaling pathway in the regulation of pyroptosis. For instance, ETS Proto-Oncogene 1 (ETS1), a transcription factor, can bind to the upstream promoter transcription site of NLRP3 and trans-activate the NLRP3 of RTEC, knockdown of ETS1 significantly inhibits pyroptosis [ 63 ]. Similarly, in LPS/ATP-induced HK-2 cells, the enhancer binding protein β (C/EBPβ) or mitochondrial transcription factor A (TFAM) is upregulated, knocking down C/EBPβ inhibits LPS combined with ATP-induced cell damage and the secretion of IL-1β and IL-18.…”
Section: Ischemia-reperfusion Injury Akimentioning
confidence: 99%